China wakes the struggle for the soul of a rising power - Kristof, Nicholas D. 1959-; WuDunn, Sheryl 1959- (Times Books, 1994)
"With the Chinese economy (the world's third largest) on a trajectory to overtake Japan and the United States in the coming decades, Kristof and WuDunn describe a spectacular economic boom that has enabled a twenty-three-year old to start his own airline or a manual laborer to become a millionaire furniture manufacturer. But they also reveal the chilling paradox lurking beneath these rags-to-riches stories: despite the stock markets and the cellular telephones, China has retained its totalitarian infrastructure, including the notorious "shackleboards" to which dissidents are strapped and brutally tortured. And with the world's largest army, the People's Republic continues to embody a tremendous challenge to the stability of the Pacific Rim." "Never before has China been portrayed so compellingly or with such feeling. As this great nation stands poised to fulfill Napoleon's prediction, China Wakes is an indispensable guide to the rumblings ahead."--BOOK JACKET.